Safety and Tolerability of Doripenem in Hospitalized Children With Complicated Intra-Abdominal Infection, Complicated Urinary Tract Infections and Pneumonia. Issue 11 (November 2015) - Cannavino, Christopher R.; Castaneda-Ruiz, Bibiana; Redman, Rebecca; Go, Oscar; Cirillo, Iolanda; Barauskas, Vidmantas; Senatorova, Ganna; Emeryk, Andrzej; Bradley, John S.
Abstract : Three multicenter, randomized, controlled studies evaluated doripenem in children 3 months to <18 years of age, with complicated intra-abdominal or urinary tract infections and bacterial pneumonia. In the 66 patients treated with doripenem before early termination of the studies for nonsafety reasons, doripenem was safe and generally well tolerated. Low enrollment limited ability to assess benefits and risks of doripenem in children. Abstract : Supplemental Digital Content is available in the text.